Experimental Demonstration of a Solar Powered High Temperature Latent Heat Storage Prototype - Asem Alemam; Nicolas Lopez Ferber; Tommy Malm; Valerie Eveloy; Nicolas Calvet (SolarPACES Conference Proceedings, 2024)
The challenge of imbalances between renewable energy supply and grid demand underscores the significance of energy storage in microgrids. This research presents an empirical assessment of the operational capabilities of a full-scale Electrical Thermal Energy Storage (ETES) prototype system named Thermal Energy Storage Power On Demand (TES.POD®), in solar-abundant and harsh desert conditions. The system incorporates a high-temperature commercial-scale latent heat thermal energy storage, integrated with a Stirling engine. Over a continuous span of 10 days, from September 26th to October 6th, 2022, the input and output power, as well as the heat transfer fluid temperatures during charging and discharging were monitored to assess the power block and system efficiencies. Results from the experiments reveal that this prototype effectively maintains a near-constant electricity production rate of 10.5 ± 1 kW for a discharge duration of 13 hours. Average cycle efficiency stands at 23%, while power block efficiency reaches 25%. These findings collectively suggest the system's potential for applications involving long duration thermal energy storage.